2018
DOI: 10.3390/ma11081310
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of Luminescent Silica Nanoparticles as New Drug Nanocarriers in Different Cancer Cell Lines

Abstract: Luminescent mesoporous silica nanoparticles, CdTeQDs@MNs@PEG1, SiQDs@Isoc@MNs and SiQDs@Isoc@MNs@PEG2, were successfully synthetized and characterized by SEM, TEM, XRD, N2 nitrogen isotherms, 1H NMR, IR, absorption, and emission spectroscopy. Cytotoxic evaluation of these nanoparticles was performed in relevant in vitro cell models, such as human hepatoma HepG2, human brain endothelial (hCMEC/D3), and human epithelial colorectal adenocarcinoma (Caco-2) cell lines. None of the tested nanoparticles showed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…MNs nanoparticles had their HD and water stability determined by DLS assays (HD = 443 ± 19 nm, PDI = 0.45 ± 0.09 and ζ = -21 ± 0.2 mV), showing similar results to those already reported for the same system, in the same conditions [37]. The successful production of silica nanoparticles was validated by their FTIR and XRD spectra.…”
Section: Synthesis Of Gold@mesoporous Silica Nanoparticles and Characterisationsupporting
confidence: 82%
See 1 more Smart Citation
“…MNs nanoparticles had their HD and water stability determined by DLS assays (HD = 443 ± 19 nm, PDI = 0.45 ± 0.09 and ζ = -21 ± 0.2 mV), showing similar results to those already reported for the same system, in the same conditions [37]. The successful production of silica nanoparticles was validated by their FTIR and XRD spectra.…”
Section: Synthesis Of Gold@mesoporous Silica Nanoparticles and Characterisationsupporting
confidence: 82%
“…The final gold concentration in AuNPs purified dispersions was obtained by ICP, with [Au] = 8.24 × 10 −4 M corresponding to an average AuNPs concentration of 9.2 × 10 11 particles/mL. Gold mesoporous nanoparticles (Au@MNs) were obtained through the growth of a silica shell by a wellestablished and reported Stöber method for the synthesis of MCM-41 [18,36,37]. Here, TEOS was used as silica source, CTAB as a cationic templating surfactant, ethylene glycol as stabiliser and NaOH as reducing and morphological agent.…”
Section: Synthesis Of Gold@mesoporous Silica Nanoparticles and Characterisationmentioning
confidence: 99%
“…Based on these previous studies, in this work, SiQDs were performed in a one-step synthesis in water using (3aminopropyl) trimethoxysilane (APTMS) and sodium ascorbate (SA) [18]. Despite all reported synthetic methods of silicon quantum dots in water [15][16][17][18][19], nanocarriers resulting from the combination of silicon quantum dots and silica mesoporous nanoparticles are yet scarce [20,21]. Additionally, from all nanocarriers developed to date that are under the preclinical stage for CRC [22][23][24][25][26][27][28][29][30][31][32][33][34][35], none combines luminescent quantum dots (silicon quantum dots) and mesoporous silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…To surmise, the delivery of anti-cancer drugs in fully non-toxic materials (non-use of toxic luminescent QDs) comprising SiQDs and mesoporous matrixes, has, according to literature [36,37], never been reported. Thus, the novelty of the work stands, despite a recent report by the authors on the sole toxicity of mesoporous SiQD-based systems [21], on the foremost development of similar nanosystems in the controlled delivery of DOX in specific cancer colorectal cell lines, for future applications as building blocks in targeted nanotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…Vallet-Regi proposed for the first time mesoporous silica nanoparticles (MSN) as controlled delivery systems [4]. Since then it was found that this type of material may be one of the greatest carrier materials for hydrophobic or hydrophilic drugs [5] due to their controlled pore size, large surface area, pore volume and, moreover, it has been demonstrated that it has very high biocompatibility both in vitro and in vivo [6]. Unlike other carriers, MSN exhibit a higher resistance to temperature and pH variation, mechanical stress and hydrolysis-induced degradations thus making a stable and rigid framework.…”
Section: Introductionmentioning
confidence: 99%